How is the Epistemology for E-learning Education? - UNAM,, SUAyED; Elenes, Evelyn (IJRDO- Journal of Educational Research, 2017)
This article works over the conception of an educative model for E-learningUniversity named Friendship Politics that is an effort to resolve in such a way the problemof Fruststrated Carreers in E learning Universitarians. For arriving here, the argumentationdeparts from making a difference in the way that learn Face to Face Scholars in relation toE-learners.